The role of FACTS devices in power system operation and control using AI techniques - Mohammed Ibrahim Mosaad Mohammed; Atef Ali Elemary; Fahmy Moutwaly Bendary; Mahmoud Mohamed Elmetwally (Cairo : Mohammed Ibrahim Mosaad Modammed, 2009)
With the rapid development of power electronices,Flexibe AC Transmission Systems(FACTS)devices have been proposed and implemented in power systems.FACTS devies can be used to control power flow and enhance system stability
Thesis (Ph.D.) - Cairo University - Faculty of Engineering - Department of Electrical Power and Machines
Issued also as CD
Keywords: Artifical Intelligent; FACTS; Optimization